High throughput screening for expanded CTG repeats in myotonic dystrophy type 1 using melt curve analysis. Issue 4 (24th February 2021) - Butterfield, Russell J.; Imburgia, Carina; Mayne, Katie; Newcomb, Tara; Dunn, Diane M.; Duval, Brett; Feldkamp, Marcia L.; Johnson, Nicholas E.; Weiss, Robert B.
Abstract: Background: Myotonic dystrophy type 1 (DM1) is caused by CTG repeat expansions in the DMPK gene and is the most common form of muscular dystrophy. Patients can have long delays from onset to diagnosis, since clinical signs and symptoms are often nonspecific and overlapping with other disorders. Clinical genetic testing by Southern blot or triplet‐primed PCR (TP‐PCR) is technically challenging and cost prohibitive for population surveys. Methods: Here, we present a high throughput, low‐cost screening tool for CTG repeat expansions using TP‐PCR followed by high resolution melt curve analysis with saturating concentrations of SYBR GreenER dye. Results: We determined that multimodal melt profiles from the TP‐PCR assay are a proxy for amplicon length stoichiometry. In a screen of 10, 097 newborn blood spots, melt profile analysis accurately reflected the tri‐modal distribution of common alleles from 5 to 35 CTG repeats, and identified the premutation and full expansion alleles. Conclusion: We demonstrate that robust detection of expanded CTG repeats in a single tube can be achieved from samples derived from specimens with minimal template DNA such as dried blood spots (DBS). This technique is readily adaptable to large‐scale testing programs such as population studies and newborn screening programs. Abstract : Myotonic dystrophy type 1 is one of the most common forms of muscular dystrophy, caused by a CTG repeat expansion in the DMPK gene. Here, we present a high throughput, low‐cost screening tool to detect an expansion of the CTG repeat using TP‐PCR followed by melt curve analysis with saturating concentrations of SYBR GreenER dye. We demonstrate that accurate and robust detection of expanded CTG repeats in a single tube can be achieved from samples derived from specimens with minimal template DNA such as dried blood spots.